Parents' perspectives about discussing climate change during well-child visits - Maya I. Ragavan; Lucy E. Marcil; Rebecca Philipsborn; Arvin Garg (Elsevier, 2021)
Objectives: The American Academy of Pediatrics recommends discussing climate change with parents, particularly at well-child visits; however, parental opinions about receiving climate change information at their child's checkup are largely unknown. This exploratory study examines: (1) parents' perspectives on frequency of climate change discussions during well-child visits and if climate change should be incorporated into well-child visits; and (2) associations between parents' perspectives about climate change and if climate change should be incorporated into well-child visits. Methods: We conducted cross-sectional surveys with parents of children 0-17; parents were recruited from the waiting rooms of two clinics and an online recruitment repository. The survey included investigator-developed questions about guidance around climate change during well-child visits and questions from the Climate Change in the American Mind survey. Descriptive statistics were used to examine frequencies, means, and standard deviations. Logistic regression was used to examine associations between perspectives about climate change and how climate change should be incorporated into well-child visits. Results: A total of 371 parents (71% of those approached) completed the survey. Four percent of parents reported that global warming was discussed during their child's well visits over the past year. Eighty percent strongly agreed or agreed that the impact of global warming on their child's health should be discussed during their well visits. Fewer thought preparing for global warming (57%), reducing global warming (55%), or talking to decision makers about global warming (38%) should be covered. There were significant positive associations between parents' perceptions about global warming and their agreement that global warming should be incorporated into well-child visits. Conclusion: Results of this exploratory study suggest parental interest in incorporating climate change into well-child visits. Further research should be conducted with a larger, more diverse population, consider perspectives of providers and children, and develop best practices for inclusion of climate change into the pediatric medical home.